The range of once‐reinforced random walk in one dimension. Issue 1 (10th July 2020) - Pfaffelhuber, Peter; Stiefel, Jakob
Abstract : We study once‐reinforced random walk on Z . For this model, we derive limit results on all moments of its range using Tauberian theory.